Greget Sere Api di Suku Bugis Sulawesi Selatan - Putri, Sulfiana Mansyur (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
The Sere Api performance in Gattareng Village became the object of research because it has the complexity of realizing an aesthetic artistic expression that is combined with the field of cultural tourism. This provides an opportunity through the Sere Api performance which is expected to have an internal and external impact on individuals or groups within the specific scope of performing arts. This research aims to explain (1) the attraction or attraction of the Sere Api performance, (2) the role of artistic expression in providing an aesthetic experience, and (3) the prospects for the Sere Api performance for tourism and cultural preservation efforts. This research uses qualitative methods on the Sere Api performance and its potential in cultural tourism. Alfred Gell's approach is used to analyze the charm of movement expressions in performances that can attract the attention of the audience, so that they can give an aesthetic impression to observers, as well as giving rise to perceptions that have implications for the tourism sector.The research results show that (1) there is an attraction or charm displayed in the Sere Api performance through the movements, costumes, presentation and rituals of the performance which are able to provide cultural therapeutic elements and provide an aesthetic experience for the audience; (2) the need for an aesthetic experience that provides a tourist attraction for the audience so as to provide encouragement to enjoy the Sere Api performance in Gattareng village; and (3) the government pays special attention to performing arts as an agent and asset for cultural tourism. The increasingly complex and routine role of performing arts opens up opportunities for collaborative work with other scientific disciplines and is able to provide hope for varied development in the use of cultural diversity in Indonesia.